Subaqueous multiscale bedform morphology dynamics in a mountainous macrotidal estuary - Ruiqing Liu; Ruiqing Liu; Heqin Cheng; Jinfeng Chen; Lizhi Teng; Zhongda Ren; Zhongda Ren; Qian Yang; Heshan Fan; Heshan Fan; Alice Lefebvre (Frontiers in Marine Science)
Bedforms in macrotidal estuaries and deltas are distinguished from those in rivers and oceans due to the tidally-driven water depth variations and the varying hydrodynamic processes resulting from the interaction between tidal and fluvial flows. The relations between hydrodynamics, sediment transport, and bedform morphology in these estuaries are complex, but research on the morphodynamics of bedforms in such environments is still lacking. This study explores the morphodynamic development patterns of multiscale bedforms in mountainous estuaries and tidal deltas, using the Minjiang Estuary as a representative case. Field observations were conducted in the Minjiang Estuary in the East China Sea in December 2021 (dry season) and August 2023 (flood season) using a multibeam echosounder system and an Acoustic Doppler Current Profiler (ADCP). Bedform presence and characteristics were calculated from bed elevation data. The results indicate that bedforms are widely developed from the underwater delta plain to the delta front channel of the Minjiang Estuary, with large compound bedforms being prevalent. Both primary and secondary bedforms coexist, with wavelengths ranging from 2 to 233 meters and heights from 0.1 to 6 meters. About 60% of primary bedforms exhibit ebb asymmetry, indicating ebb-directed sediment transport in the main channel. The average flood/ebb lee side angle is 6°, with an average maximum angle of 19°. The maximum side angle of primary bedforms is observed to be on average greater than that of secondary bedforms. Water depth and riverbed slope significantly affect bedform density, with non-sloping riverbeds favoring bedform development. Variations in bed shear stress throughout the tidal cycle drive differences in bedform size and morphology. High clay content in surface sediments correlates with lower bedform density, indicating fine-grained materials may inhibit bedform development. This study highlights a feedback mechanism where structural geology shapes channel morphology, influencing energy distribution and bedform evolution. The findings enhance our understanding of sediment transport and hydrodynamic processes in macrotidal estuaries, offering insights for estuarine management and conservation. Future research should explore how seasonal and tidal variations influence bedform evolution to refine models of estuarine dynamics.